Reconstruction of Anti-Hail System in Kakheti (Georgia) - Amiranashvili, AvtandilG.; Chikhladze, VictorA.; Dzodzuashvili, Ucha V.; Ghlonti, Nugzar Ya.; Sauri, Ioseb P. (Journals of Georgian Geophysical Society, 2016)
Large-scale experimental, experimental-production and production work on action on hail processes in Georgia was conducted in 1960-1989 (Kakheti, Southern Georgia) over the total area of approximately 1.2 million hectares. Positive effect changed in interval of 20 - 95% with average value of 75 - 85%. In those following quarter of century, after the curtailment of these works, damage to agriculture from the hail grew and returned to the level, which was to the beginning of anti-hail works. In 2015 year in Kakheti over the area of approximately 650 thousand hectares the work on actions on hail processes were renewed. The description of the restored anti-hail system is given which includes: contemporary meteorological radar Meteor 735CDP10 of firm Selex ES; central remote-control station with the change personnel; the automated system of the fire control; 85 rocket launching sites; the autonomous automated rocket guns; anti-hail rockets; scientific group; the group of the maintenance of radar and rocket guns. The test probation of system showed the prospect of its further use for dealing with the hail. The physical and economic effectiveness of anti-hail works in 2015 year, in spite of the limited quantity of means of action (rockets), it was not worse than it is earlier in the years with the action. It is significant that if in the past in Kakheti personnel of anti-hail service comprised more than 800 people, at present this work it ensures only 30 people. Subsequently is assumed an increase in the shielded from the hail areas, and also, besides the anti-hail works, the use of radar for monitoring of dangerous hydrometeorological processes in eastern Georgia and adjacent to its territories of Armenia and Azerbaijan.